Military spending and the risks of coups d'etats - Collier, P; Hoeffler, A (2007)
The governments of many developing countries face a risk of a coup d'’état perpetrated by their own military establishment. The phenomenon is especially acute in Africa. We decompose the risk into its component parts: the risk of a plot; the risk that a plot will mature into an attempt; and the risk that an attempt with succeed; and analyze theoretically and empirically the interdependence between these risks and military spending. Since governments can be presumed to want to reduce the risk of a coup, we investigate how they might adjust military spending. We show that although the response might be either to reduce or increase spending, the expected relationship is nonmonotonic, with governments reducing spending until a threshold level of risk is reached above which they increase it. Using both global and Africa-specific data sets we model the interdependence empirically. We find that in countries with low coup risk governments react to it by cutting military spending. However, when coup risk is high, as in Africa, governments respond by increasing spending. An implication is that in these high-risk environments external security protection against coups might reduce military spending.